Rock indentation : experiments and analyses. - Murthy, Chivukula S.N. ([S.l.] : CRC Press, 2021)
This book focusses on rock indentation and importance of specific drilling/cutting energy as a performance indicator for drilling/rock cutting. It aids in designing of drill bits and cutting picks, through performance evaluation for a given geometry. It further covers stress distribution along three axes in rock during load application, correlation of specific energy with properties of rocks and statistical modelling to generate mathematical equation to estimate the specific energy indentation, including performance prediction by artificial neural network modelling. Presented models can be used to assess the specific energy in rock indentation from the physic-mechanical properties of rocks. Presents synthesis of rock indentation experiments and analyses Deals with statistical modeling to generate mathematical equations to estimate the specific energy indentation from the rock parameters/properties Discusses how to find the performance of drill and cutting bits during drilling or cutting operations through indentation test Covers numerical modeling to explain stress distribution in rock during rock indentation Includes artificial neural network concepts used in field of rock mechanics This book is aimed at researchers and graduate students in mining/geological engineering, and mechanical engineering.
OCLC-licensed vendor bibliographic record.
Keywords: Rock mechanics; Rocks -- Testing; TECHNOLOGY / Engineering / Civil